The infinite moment of us - Myracle, Lauren, 1969- (Amulet Books, 2013)
As high school graduation nears, Wren Gray is surprised to connect with gentle Charlie Parker, a boy with a troubled past who has loved her for years, while she considers displeasing her parents for the first time and changing the plans for her future.